Honey Bee Survival and Flight Capacity After Exposure to Sulfoxaflor Residues - Ewerton Marinho da Costa; Letícia Pinheiro Augusto; Emanoely Karoliny Santos da Silva; Victor Hugo Martins Rocha; Tiago Augusto Lima Cardoso; Elton Lucio Araujo; Fernandes Antonio de Almeida (Sociobiology)
Knowing the toxicity of insecticides used for pest control in melon on the bee Apis mellifera is essential for the conservation of this species in production areas, thus enabling the conciliation of insecticide applications with the sustainable use of pollinators in the field. From this perspective, this study aimed to evaluate the survival and flight ability of A. mellifera after exposure to residues of the insecticide Sulfoxaflor on melon leaves. The bioassay was conducted under laboratory conditions, in a completely randomized design set up in a 3 x 6 factorial arrangement, represented by two doses of the insecticide Sulfoxaflor (0.048 and 0.192 g i.a./L), one control (distilled water), and six exposure times after application of the product on melon leaves: immediately after spraying and 1h, 2h, 3h, 24h, and 48h after spraying. The insecticide Sulfoxaflor caused 100% morality in the bees exposed to the dose of 0.048 g i.a./L in the periods immediately after spraying and 1h, 2h, and 3h after spraying. The dose of 0.192 g i.a./L, regardless of the exposure time after spraying, resulted in 100% mortality. The median lethal time (TL50) provided by the Sulfoxaflor doses were significantly lower compared to the control, regardless of the time after foliar spraying. Sulfoxaflor negatively affected the flight ability of surviving bees. Regardless of the dose and exposure time after spraying, Sulfoxaflor was highly toxic via residues to A. mellifera under laboratory conditions.